Combustion characteristics study of biomass in a fluidized bed combustor - Abdullah, Haryati; Ani, Farid Nasir; Mohd. Jaafar, Mohammad Nazri (Universiti Teknologi Malaysia, 2005)
This report summarizes the research work carried out in studying the combustion characteristics of biomass in a fluidized bed combustor. The study was carried out using the air staging technique to control and reduce the emissions from the combustion of biomass. The gaseous emissions studied include nitrogen oxide, NOx and carbon monoxide, CO. Fluidized bed combustion has been recognized as a technology that can generate power from solid wastes and more importantly it has been known as a suitable combustion system for biomass. The objective of this research is to study the effect of using the air-staging technique on the combustion characteristics including the effect on the gaseous emissions from a fluidized bed combustor firing biomass waste as a source of fuel. In this research work, palm shell is used as the source of fuel. This report describes the results obtained and the methodology adopted. Air staging is achieved by dividing the total combustion air supply into the in-bed primary air and the secondary air. The secondary air is injected into the freeboard. The study was carried out based on the ratio of the secondary air to the total combustion air which was varied from 0 to 0.4 and by taking into consideration the percentage of excess air. The outcome of this research work has shown that air staging affects the temperature distributions as well as the combustion efficiency. It also indicates that significant reductions in NOx emissions were obtained for the staged operation when compared to the un-staged operation. The CO emission was mostly affected by the percentage of excess air. This significant reduction is a clear indication of the prospect of using this technology for sustainable management of the environment and a better future for our palm oil industry.